Carbon chemical speciation and polymerization in liquid metals - Devyesh Rana; Emma Egli; Lourdes Salamanca-Riba; Steven R. Lustig (Carbon Trends, 2025)
Understanding the chemical speciation and thermodynamics of metal-carbon polymerization in liquid metals such as aluminum, copper, and silver is critical to advancing carbon-based materials with unique properties. Metalocarbons, low molecular weight metal-carbon species, are identified using ab initio molecular dynamics (AIMD) by monitoring the long-time evolution of thermodynamically favored species within explicit metal atom solvent. Thermochemical analysis predicts that metalographene structures are thermodynamically more stable than smaller metalocarbon species, suggesting that metalocarbons can be polymerized into larger metalographenes in liquid aluminum, copper, and silver solutions. We identify the influence of charge and electric field on the metal solution reaction mechanism thermodynamics. Redox reactions greatly affect the step addition equilibrium constants. The COnductor-like State MOdel (COSMO) of solvation and AIMD predict aluminum-carbon vibrational spectra from inelastic neutron scattering (INS) within liquid metal and solid metal compositions. An experimental INS spectrum of an aluminum covetic with 3 wt% carbon matches specific aluminographenes. The findings highlight a novel methodology for synthesizing and characterizing carbon-metal hybrid materials, offering significant implications for graphene production, sustainable materials design, and advanced applications in energy storage, electronics, and environmental technologies.